Large transmission cluster of acute hepatitis C identified among HIV‐positive men who have sex with men in Bangkok, Thailand. (20th July 2020) - Han, Win M.; Colby, Donn J.; Khlaiphuengsin, Apichaya; Apornpong, Tanakorn; Kerr, Stephen J.; Ubolyam, Sasiwimol; Kroon, Eugène; Phanuphak, Nittaya; Vasan, Sandhya; Matthews, Gail V.; Avihingsanon, Anchalee; Ruxrungtham, Kiat; et al.
Abstract: A rapidly emerging and highly concentrated hepatitis C virus (HCV) outbreak has recently been observed among both acute and chronic HIV‐positive men who have sex with men (MSM) in Bangkok, Thailand. NS5B regions of the HCV genome were amplified using nested PCR and sequenced. Phylogenetic inference was constructed by Maximum Likelihood methods and clusters were identified with support and genetic distance thresholds of 85% and of 4.5%. Forty‐eight (25 acute HIV and 23 chronic HIV) MSM with incident HCV infection were included in the analysis. HCV genotype (GT) was 85% GT 1a and 15% GT 3a or 3b. Median age at HCV diagnosis was 34 (interquartile range, 28‐41) years. 83.3% (40/48) had history of syphilis infection and 36% (16/44) reported crystal methamphetamine use. Only 2 (4%) reported ever injecting drugs, both crystal methamphetamine. In the phylogenetic clustering analysis, 83% belonged to one of two clusters: one large (75%) and one small (8%) cluster. All clusters were GT 1a. MSM with acute HIV infection were more likely to be in a cluster (92%) than those with chronic infection (74%). HCV screening should be regularly performed for MSM in ART clinics, and offering direct‐acting antiviral agents to all MSM with HCV infection might contain the HCV epidemic from expanding further.